Pengaruh Online Review dan Citra Merek terhadap Niat Menginap Wisatawan di Hotel The Haven Legian - Sharon Charmelita Budiarto; Kadek Wiwik Handayani; Ni Made Dwila Santi; Kadek Agus Wira Antara; Putu Laksmita Dewi Rahmayanti; Nyoman Surya Wijaya (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2023)
Covid-19 has had a major impact on the tourism sector. The hospitality industry is one of the most significant contributions to the Indonesian economy. One of the hospitality companies in Bali is Hotel The Haven. The Haven Hotel is a commercial establishment providing lodging, meals and other for guest service. However, currently the industry hospitality is already in recovery. This study aims to explain the effect of online review and brand image to stay intentions at The Haven Hotel. The type of research used is associative research, with sampling using non- probability techniques with purposive sampling method, on respondents who are tourist visitors to The Haven Hotel Legian. Quantitative data analysis technique uses linear regression with SPSS 25.0 software. The results of this study provide several conclusions, online review has a positive and insignificant effect on  intention to stay, and brand image has a positive and significant effect on intention to stay.